STUDI PERBANDINGAN ANTARA ALGORITMA BIVARIATE MARGINAL DISTRIBUTION DENGAN ALGORITMA GENETIKA - Fatichah, Chastine; Kusuma, Imam Artha; Purwananto, Yudhi (Institute of Research and Community Outreach - Petra Christian University, 2006)
Bivariate Marginal Distribution Algorithm is extended from Estimation of Distribution Algorithm. This heuristic algorithm proposes the new approach for recombination of generate new individual that without crossover and mutation process such as genetic algorithm. Bivariate Marginal Distribution Algorithm uses connectivity variable the pair gene for recombination of generate new individual. Connectivity between variable is doing along optimization process. In this research, genetic algorithm performance with one point crossover is compared with Bivariate Marginal Distribution Algorithm performance in case Onemax, De Jong F2 function, and Traveling Salesman Problem. In this research, experimental results have shown performance the both algorithm is dependence of parameter respectively and also population size that used. For Onemax case with size small problem, Genetic Algorithm perform better with small number of iteration and more fast for get optimum result. However, Bivariate Marginal Distribution Algorithm perform better of result optimization for case Onemax with huge size problem. For De Jong F2 function, Genetic Algorithm perform better from Bivariate Marginal Distribution Algorithm of a number of iteration and time. For case Traveling Salesman Problem, Bivariate Marginal Distribution Algorithm have shown perform better from Genetic Algorithm of optimization result. Abstract in Bahasa Indonesia : Bivariate Marginal Distribution Algorithm merupakan perkembangan lebih lanjut dari Estimation of Distribution Algorithm. Algoritma heuristik ini mengenalkan pendekatan baru dalam melakukan rekombinasi untuk membentuk individu baru, yaitu tidak menggunakan proses crossover dan mutasi seperti pada Genetic Algorithm. Bivariate Marginal Distribution Algorithm menggunakan keterkaitan pasangan variabel dalam melakukan rekombinasi untuk membentuk individu baru. Keterkaitan antar variabel tersebut ditemukan selama proses optimasi berlangsung. Aplikasi yang dibuat dalam penelitian ini ditujukan untuk membandingkan kinerja Genetic Algorithm sederhana persilangan satu titik dengan Bivariate Marginal Distribution Algorithm pada kasus Onemax, Fungsi De Jong F2, dan Traveling Salesman Problem. Dari uji coba yang dilakukan, didapat hasil bahwa kinerja dari kedua algoritma tersebut dipengaruhi oleh parameter masing-masing dan juga besar ukuran populasi yang digunakan. Untuk kasus Onemax dengan ukuran masalah yang kecil, Genetic Algorithm lebih unggul dalam hal jumlah iterasi yang lebih sedikit dan waktu yang lebih cepat untuk mendapat hasil optimal. Namun, Bivariate Marginal Distribution Algorithm lebih unggul dalam hal hasil optimasi pada kasus Onemax dengan ukuran masalah yang lebih besar. Untuk Fungsi De Jong F2, Genetic Algorithm lebih unggul dari Bivariate Marginal Distribution Algorithm utamanya dalam hal jumlah iterasi dan waktu. Sedangkan untuk kasus Traveling Salesman Problem, Bivariate Marginal Distribution Algorithm dapat menunjukkan kinerja yang lebih baik dari Genetic Algorithm dalam hal hasil optimasi. Kata kunci: heuristic algorithm, estimation of distribution algorithm, bivariate marginal distribution algorithm, genetic algorithm.